Am I Creating A Safe Space? - Gomathi Jatin
The concept of “safe space” dates back to the 1970s when it was used to describe the physical space where individuals could share their experiences in a safe environment (Flensner & Von der Lippe, 2019). Though a fundamental requirement of a safe space is physical safety, we should recognize that a learning space that is free from violence, discrimination, harassment, and fear; encourages participation and honest sharing of ideas; is non-judgmental, characterized by respect, and allows risk-taking, promotes healthy, positive and flourishing educational experiences. Academic safe space aims to create an inclusive and effective learning environment in a complex learning environment (Magdola, 2000, p. 94 as cited in Gayle, Cortez & Preiss, 2013). The Sustainable Development Goals (SDGs), also known as the Global Goals, adopted by the United Nations in 2015 as a universal call to ensure peace and prosperity for all by 2030, aims to address various social, economic, and environmental challenges through the essential tenets of diversity and inclusion. In this context, the author in this paper brings to the forefront a very nagging and persistent question for educators asking them to reflect on the question “Am I creating a Safe space?” and recommends strategies for creating that “safe space” for learners․
Keywords: Education